Synthesis of Sterically Hindered Allylboranes via Ru-Catalyzed Reductive Boration of Propargylic Acetates - Chen, Liang; Sun, Jianwei (Synlett, 2025)
A ruthenium-catalyzed selective synthesis of sterically hindered allylboranes is disclosed. Starting from readily available propargylic acetates, this process proceeded via initial reduction to the corresponding allenes followed by α-selective hydroboration. The choice of a suitable catalyst that can catalyze both steps is crucial to success. This process enjoys easy substrate preparation. It serves as a promising starting point for the further development into more practical synthesis of valuable hindered allylboranes.
Keywords: Hydroboration; Allylborane; Ruthenium; Regioselectivity; Propargylic compound